PD-L1/PD-1 Expression in Endometrial Clear Cell Carcinoma: A Potential Surrogate Marker for Clinical Trials. (February 2020) - Jin, Cao; Hacking, Sean; Liang, Sharon; Nasim, Mansoor
Background . Endometrial clear cell carcinoma (ECCC) represents a rare subtype of endometrial cancer. Recently, immunotherapeutic drugs targeting programmed cell death protein 1 (PD-1)/programmed death ligand-1 (PD-L1) was associated with improved survival in several types of cancer (especially in patients with mismatch-repair (MMR)-deficient status). The aim of this study is to evaluate the correlation between the PD-L1/PD-1 axis and clinical and pathological features in strictly defined ECCC diagnosed at our institution. Design . Review of ECCC (diagnosed in the period of 2000 to 2017) identified 23 cases (n = 23) in our institution. The cases were reviewed by 2 gynecological pathologists. Estrogen receptor, progesterone receptor, napsin A, p16, and p53 were also performed so that only pure CCC cases were included. PD-L1 (SP142), PD-1, and MMR antibodies were performed. PD-L1 and PD-1 were scored in both the tumor and the peritumoral lymphocyte infiltration. Clinical and pathological features were recorded to correlate with the expression of the 2 markers. Results . Among the 23 cases, 20 cases were qualified for pure CCC by histology and immunohistochemistry patterns. Regarding PD-1 expression, 6/20 (30%) patients had positive expression in peritumoral lymphocyte infiltration. While 3/20 (15%) cases had PD-L1 either tumoral or peritumoral lymphocytes expression. Loss of MMR expression was present in 1 (5%) of 20 patients. PD-1 and/or PD-L1 expression cases tended to have deeper myometrial invasion and higher stage at presentation. Conclusions . Our results are suggestive of the roles of both PD-1 and PD-L1 in ECCCs as useful therapeutic biomarkers for immunotherapy.